THE EFFECTIVENESS OF USING TIKTOK ON STUDENTS' ENGLISH ACHIEVEMENT AT SMKN 8 MAJENE - Sarkiah Sarkiah; Rafi’ah Nur; Salasiah Ammade; Ammang Latifa; Siti Hajar Larekeng (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
English proficiency is necessary in our globalized era for both career advancement and academic achievement. Teachers at SMKN 8 Majene have tried a variety of educational approaches, but students' English language achievement has continuously lagged below the average of 5.5. The purpose of this study is to determine whether employing TikTok as a learning tool may improve students' engagement and English language proficiency. 32 students from SMKN 8 Majene's class XI participated in a quasi-experimental design. TikTok was a learning aid employed by the experimental group, whilst conventional teaching techniques were used by the control group. To gauge the learning outcomes, both groups received pre- and post-tests.The average post-test scores of the experimental group were significantly higher (69.2) than those of the control group (64.0). The results suggest that TikTok effectively enhances student engagement and English language achievement